2019
DOI: 10.1080/13880209.2019.1626447
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyshikonin isolated from Arnebia euchroma inhibits colorectal cancer by down-regulating the PI3K/Akt/mTOR pathway

Abstract: Context: Shikonins, a series of natural occurring naphthoquinones extracted from Arnebia euchroma (Royle) Jonst. (Boraginaceae), have antitumor activities and low toxicity. Objective: To illuminate potential activity and mechanism of shikonins against colorectal cancer (CRC). Materials and methods: Five shikonins were isolated from A. euchroma , and elucidated by extensive spectroscopic analysis. Anti-proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Deoxyshikonin is found in Lithospermum erythrorhizon and a promising drug candidate for the treatment of wounds and cancers [ 41 , 42 ]. Deoxyshikonin is a derivative of shikonin, which is a well-known traditional Chinese medicine that has long been used for the treatment of burns, external wounds, infected crusts, and hemorrhoids owing to its numerous pharmacological properties [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deoxyshikonin is found in Lithospermum erythrorhizon and a promising drug candidate for the treatment of wounds and cancers [ 41 , 42 ]. Deoxyshikonin is a derivative of shikonin, which is a well-known traditional Chinese medicine that has long been used for the treatment of burns, external wounds, infected crusts, and hemorrhoids owing to its numerous pharmacological properties [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acetylshikonin, another shikonin derivative, significantly inhibited the anchorage-independent growth of pancreatic cancer cells by suppressing the nuclear factor-kappa B signaling pathway ( 27 ). More importantly, it was previously demonstrated that deoxyshikonin exhibited anti-proliferative and pro-apoptotic activities in colorectal cancer cells through the phosphoinositide 3-kinase (PI3K)/Akt/mTOR pathway ( 10 ). Nevertheless, whether deoxyshikonin showed an anti-tumor activity in AML remained far from being addressed.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of researches reveal that shikonin derivatives have garnered much research interest due to its limited toxicity and stronger anti-tumor activities in miscellaneous cancers ( 9 ). Interestingly, a previous investigation proved that deoxyshikonin (its chemical structure is shown in Figure 1 ), a derivative of shikonin, exhibited an anti-tumor effect in colorectal cancer ( 10 ). However, no studies are available to illustrate the effect of deoxyshikonin on AML.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that both derivatives increased the percentage of JVM-13 cells in the G0/G1 phase ( Figure 4 b), while the percentage of BCL1 cells in the G0/G1 phase was increased after MBS treatment ( Figure 4 a). Cyclin D3 binds to CDK4 and CDK6 and plays a role as the initial activator of the G1 phase [ 28 , 29 , 30 , 31 ]. In line with this, MBS treatment induced a decrease in the mRNA level of cyclin D3 in BCL1 cells ( Figure 4 c) and the percentage of cyclin D3 expressing JVM-13 ( Figure 4 d) but significantly enhanced the expression of the protein level of the inhibitor of cyclin D–CDK4/CDK6 complex, p16 [ 28 ], the universal cyclin-CDK inhibitor, p21 [ 29 ], and the inhibitor of cyclin E-CDK2, cyclin A-CDK2, and cyclin D-CDK4 complexes, p27 [ 30 ], in BCL1 cells ( Figure 4 e).…”
Section: Discussionmentioning
confidence: 99%